Prognostic significance of non-sustained ventricular tachycardia on stored electrograms of heart failure patients with cardiovascular implantable electronic devices. (14th October 2021) - Barradas Da Silva, M; Duarte, F; Oliveira, L; Serena, C; Fontes, A; Monteiro, A; Machado, C; Dourado, R; Santos, E; Pelicano, N; Pacheco, M; Tavares, A; et al.
Abstract: Background: Non-sustained ventricular tachycardia (NSVT) is commonly found in patients with structural heart disease and was historically obtained from registers of external ambulatory monitoring. The advent of Cardiac implantable electronic devices (CIEDs) has made it possible to detect asymptomatic NSVT in Heart Failure (HF) patients more frequently, but its true impact in real world is uncertain, and often does not lead to a change in clinical intervention. Purpose: To determine the prognostic significance of NSVT detection on stored electrograms of CIEDs in HF patients with systolic left ventricle dysfunction. Methods: We retrospectively enrolled 132 consecutive HF patients (mean age 67, 5±11, 1 years, males 72, 0%) with systolic left ventricle dysfunction and CIEDs (biventricular pacemakers with or without cardiac defibrillators). Patients were evaluated through CIEDs interrogation and clinical evaluations and divided into NSVT positive (Group 1) and negative groups (Group 2). Mean follow-up period was 62, 8±7, 1 months. Results: NSVT was detected in 51 (38, 6%) patients. 70 (53, 0%) had implantable cardiac resynchronization therapy (CRT) defibrillator (CRT-D), 37 (28, 0%) transvenous implantable cardioverter defibrillator (ICD), 13 (9, 8%) CRT pacemaker (CRT-P) and 12 (9, 1%) subcutaneous ICD (S-ICD). Medium left ventricular ejection fraction (LVEF) was 31, 1±7, 9%, 20, 6% were in NYHA III-IV and 47, 0% were ischemic (49% Group 1 and 45, 7% Group 2, p=0, 708). Dyslipidemia was more prevalent in Group 2 (p=0, 042). In total 11 (8, 3%) patients died, 2 (1, 5%) from sudden cardiac death and 5 (3, 8%) from cardiovascular death. NSVT was associated with CIEDs treatments (hazard ratio [HR]2, 52; 95% confidence interval [CI]1, 2–5, 1; p=0, 001), ventricular fibrillation (VF) (HR: 3, 71, 95% CI: 1, 19–11, 58; p=0, 018), sustained ventricular tachycardia (VT) (HR: 9, 06, 95% CI: 2, 82–29, 12; p<0, 05) and composite outcome of VT, VF, HF re-admissions and related admissions to emergency department (ED) and death by all causes (HR: 2, 52; 95% CI: 1, 20–5, 10; p=0, 011). NSVT at 1 year was associated with HF readmissions at 1 year (p=0, 004). Conclusions: On extended monitoring possible with CIEDs, NSVT in HF patients was associated with a worse prognosis and may serve as a predictor of significant arrhythmic events, HF hospitalizations and mortality. These findings enhances the importance of remote monitoring and optimization of therapeutic modalities in these patients along with a close supervision. Funding Acknowledgement: Type of funding sources: None.